Mesenchymal cystic hamartoma of the lung: a rare cause of relapsing pneumothorax - van Klaveren, R J (1994)
A 14 year old boy is described with recurrent spontaneous pneumothoraces due to a mesenchymal cystic hamartoma, a very rare disease with a multicentric nature and a benign course in most patients.